2012
DOI: 10.1016/j.ceramint.2011.10.082
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of cubic structure in Mn-doped hafnia

Abstract: The compounds Hf1−xMnxO 2−δ (x = 0 ∼ 0.5) have been synthesized by conventional solid state reaction method in Ar. Rietveld analysis of X-ray diffraction data has shown that the Mn-doped HfO2 undergoes a structural transformation from monoclinic to cubic phases, which is significantly dependent on the Mn content under current synthesis conditions. The stabilized cubic structure by multivalent Mn ion doping can transform to the monoclinic structure when annealed at high temperature in air. Transmission electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Indeed, the crystal phase transition from their monoclinic to the cubic arrangement can be achieved at low temperature by doping. In the literature, the origin of the stabilization of high‐temperature cubic phase in HfO 2 is related to both the dopant ion size and to the oxygen vacancies concentration, depending on the valence of the dopant substituting for Hf in the lattice . For instance, the stabilization of the cubic phase in these systems can be achieved through the incorporation of trivalent or divalent ions into the lattice, and the subsequent generation of oxygen vacancies for charge compensation .…”
Section: Materials Composition Morphology and Structurementioning
confidence: 99%
“…Indeed, the crystal phase transition from their monoclinic to the cubic arrangement can be achieved at low temperature by doping. In the literature, the origin of the stabilization of high‐temperature cubic phase in HfO 2 is related to both the dopant ion size and to the oxygen vacancies concentration, depending on the valence of the dopant substituting for Hf in the lattice . For instance, the stabilization of the cubic phase in these systems can be achieved through the incorporation of trivalent or divalent ions into the lattice, and the subsequent generation of oxygen vacancies for charge compensation .…”
Section: Materials Composition Morphology and Structurementioning
confidence: 99%
“…Gao et al have reported the synthesis at 1400°C of micrometric particles of HfO 2 using a solid-state reaction [8]. HfO 2 nanoparticles in the size range of 25-75 nm were prepared by precipitation [9] and sol-gel [10] in the temperatures range of 500-800°C.…”
Section: Introductionmentioning
confidence: 99%
“…The study on the cubic HfO 2 -R 2 O 3 (R = Lu, Ho, Gd, Sm, Yb, Y and Sc) with R ?3 ions has revealed that the deep vacancy trapping leads to the decrease in the ionic conductivity at high dopant concentrations [6]. A recent study on the Mn-doped HfO 2 [5] reveals the fact that the Mn-dopant stabilizes the cubic phase of hafnia. The variable valences of Mn lead to the different ionic-sizes of Mn and the oxygen vacancies play an important role to stabilize the cubic phase.…”
Section: Introductionmentioning
confidence: 98%
“…At room temperature, ZrO 2 (baddeleyite) and isomorphous It has been observed that the property of the doped system gets modified significantly from its pure analogue in most of the cases [4]. There have been a number of studies on the stabilization of the high-temperature phases by doping with the suitable elements [5]. The doping with a tetravalent cation (same valence as of Hf 4?…”
Section: Introductionmentioning
confidence: 98%